Asymmetric 3D Elastic–Plastic Strain‐Modulated Electron Energy Structure in Monolayer Graphene by Laser Shocking. Issue 19 (29th March 2019) - Motlag, Maithilee; Kumar, Prashant; Hu, Kevin Y.; Jin, Shengyu; Li, Ji; Shao, Jiayi; Yi, Xuan; Lin, Yen‐Hsiang; Walrath, Jenna C.; Tong, Lei; Huang, Xinyu; Goldman, Rachel S.; et al.
Abstract: Graphene has a great potential to replace silicon in prospective semiconductor industries due to its outstanding electronic and transport properties; nonetheless, its lack of energy bandgap is a substantial limitation for practical applications. To date, straining graphene to break its lattice symmetry is perhaps the most efficient approach toward realizing bandgap tunability in graphene. However, due to the weak lattice deformation induced by uniaxial or in‐plane shear strain, most strained graphene studies have yielded bandgaps <1 eV. In this work, a modulated inhomogeneous local asymmetric elastic–plastic straining is reported that utilizes GPa‐level laser shocking at a high strain rate (dε/d t ) ≈ 10 6 –10 7 s −1, with excellent formability, inducing tunable bandgaps in graphene of up to 2.1 eV, as determined by scanning tunneling spectroscopy. High‐resolution imaging and Raman spectroscopy reveal strain‐induced modifications to the atomic and electronic structure in graphene and first‐principles simulations predict the measured bandgap openings. Laser shock modulation of semimetallic graphene to a semiconducting material with controllable bandgap has the potential to benefit the electronic and optoelectronic industries. Abstract : Both the bandgap structure and the Fermi level of monolayer graphene are modulated using an easy and effective optomechanical method. Laser‐shock‐induced 3D nanoshaping enables an asymmetric elastic–plastic straining of graphene, resulting in a wide graphene bandgap of over 2.1 eV and a wide Fermi level adjustment range of 0.6 eV.